DIFFERENTIAL APPROACH IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION TEACHERS (Physical Culture and Sport: Scientific Perspective, 2022)
The stages of the future physical education teachers career formation in the Ukrainian higher education system are analyzed, the content and structure of the future physical education teachers career formation are defined and proved; the most essential directions in improving the content structure of sports and teacher education are highlighted.Social and political processes taking place in the modern Ukrainian society show that the faster it moves through scientific and technological progress, improving the welfare of citizens, the more significant is the question of formation the spiritual, mental and physical health of the future teacher, in particular the specialist in physical education. However, in addition to acquiring profound professional knowledge, specialist in physical education should be able to demonstrate his citizenship position and defend the public interests, build and assert personal relationships, self-assert in the process of professional activity, and fully meet the level of modern requirements imposed by new social and economic conditions of modern Ukrainian society. The concept of «pedagogical conditions» is extensively used in the dissertations on the problems of future specialists’ professional training, and therefore it is considered to be appropriate to conduct a deeper methodological analysis of the phenomenon.Analysis of psychological and pedagogical literature indicates that the formation process of any skill can be effectively realized only under certain conditions that reflect its essence and specificity. It is well known that any science as a special form of thought, awareness of a sphere of objective reality has its own peculiar categorical apparatus.There are many scientific approaches to the interpretation of the term "condition". In philosophical dictionary, the term "condition" is considered as a factor (Lat. Factor), that is the driving force, the reason of any process.
Keywords: professional training; career formation; professional development; system of training; educational process; physical education teachers; core subjects